Sex determination and sex ration distortion in the mosquito Aedes aegypti - Teo, TM (2010)
Aedes aegypti is one of the most important mosquito vectors of human disease, transmitting dengue, Chikungunya and yellow fever viruses. New control methods are much needed for this species and an ability to skew sex ratios toward males would be very useful for a number of strategies. In this study, male-specific chromosomal regions were searched for in Ae. aegypti using novel approaches such as microdissection of chromosomes. The sex determination pathway of Ae. aegypti was also explored, using Drosophila melanogaster as a model, to find candidate genes that could be used to induce male biased sex ratios. The transformer-2 (tra-2) gene is necessary for sexual differentiation of females in D. melanogaster, but its role remains unknown in mosquitoes. A homolog of tra-2 was identified in Ae. aegypti. Rapid Amplification of cDNA ends (RACE) experiments were conducted to characterize this gene in Ae. aegypti. The Ae. aegypti tra-2 gene, as for D. melanogaster, was highly variable in transcription due to alternative splicing and alternative polyadenylation, with 9 different variants identified. RNA interference (RNAi) was then used to determine if knockdown of all variants of Ae. aegypti tra-2 can be achieved and if it would cause gender switching in individuals, initially by means of direct injection of double stranded RNA, and then progressing to germline transformation. A construct designed to produce tra-2 dsRNA was injected into Ae. aegypti embryos and integrated into the Ae. aegypti genome. The transgenic population showed up to 100% male bias in single pair crosses. The male bias effect could still be seen in the heterozygous population. The results suggest that knockdown of tra-2 could provide a useful tool for sex ratio distortion as part of the development of novel control methods for Ae. aegypti.